Community Participation in Village Infrastructure Development Planning - Achmalul Jannah; Isnaini Rodiyah (Indonesian Journal of Cultural and Community Development, 2021)
The purpose of this study was to describe and analyze community participation in infrastructure development planning in Panggreh Village, Jabon District, Sidoarjo Regency. This research method uses a qualitative descriptive method. Data collection techniques through interviews, observation, and documentation. Data analysis techniques through data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that community participation in infrastructure development planning in Panggreh Village is divided into five stages. In the first stage, namely the formation of the RPJM drafting team for Panggreh Village, the people involved were internal community groups. The second stage is hamlet meetings with community participation in the form of attendance and making proposals related to development planning and analyzing environmental conditions. The third stage is the Village Musrenbang, community participation in the form of extracting ideas and forms of energy. The fourth stage is the drafting of a community participation development plan that has been represented by the BPD. The fifth stage, namely the determination of the Village RPJM, community participation is also represented by the BPD.